Performance comparison between RGB and HSI linear stretching for tuberculosis bacilli detection in ziehl-neelsen tissue slide images - Osman, M. K.; Mohd Yusoff, Mashor, Prof Madya Dr.; Jaafar, H.; Rafikha Aliana, A. Raof; Nor Hazlyna, Harun (Institut of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/